Identification of a degrading enzyme in human serum that hydrolyzes a C‐terminal core sequence of neuromedin U. Issue 4 (4th November 2016) - Takayama, Kentaro; Taguchi, Akihiro; Yakushiji, Fumika; Hayashi, Yoshio
ABSTRACT: Neuromedin U (NMU), an anorexigenic peptide, has attracted attention as a candidate for development of drugs against obesity. We recently developed several potent hexapeptidic agonists derived from NMU that share a common Pro‐Arg‐Asn‐NH2 (PRN) sequence at their C‐termini and found that the amide bond between Arg and Asn is rapidly degraded in serum. In this study, we determined that the key enzyme responsible for this biodegradation was thrombin. Both irreversible and reversible thrombin inhibitors (PPACK and argatroban, respectively) enhanced the serum stability of both hexapeptidic agonists and human NMU itself as an inherent ligand. In addition, rapid degradation did not occur in citrated human plasma because thrombin was not activated under these conditions. Furthermore, we found that an N‐terminal 2‐thienylacetyl group in hexapeptidic agonists enhanced recognition by thrombin. These findings will be valuable for future investigations of the biological functions of NMU in vivo. © 2015 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 106: 440–445, 2016.